DEVELOPMENT OF FUN THINKERS BOOK LEARNING MEDIA IN SOCIAL STUDIES CLASS VII MTS ASHRI SUBJECTS - Miftahul Khotimah; Anindya Fajarini (SOLIDARITY: Journal of Social Studies, 2022)
The limited use of learning media that is less effective causes the learning process to become a problem for students. this makes teaching and learning activities boring. Development of media fun thinkers book to assist the availability of learning media and motivation to participate in teaching and learning activities for social studies subjects. This research purpose: 1) Produce products for the development of social science learning media fun thinkers book for class VII at MTs ASHRI for 2020/2021. 2) Knowing the validity of the product development of social science learning media fun thinkers book class VII at MTs ASHRI for 2020/2021. The method used is R&D, the ASSURE development model. Collecting data using questionnaires and interviews. The research subjects were social studies teachers and 35 seventh-grade students. Data analysis using qualitative and quantitative techniques. The results showed that: (1) material expert validation I with a score of 80.76% "quite valid", (2) material expert validation II with a score of 71.15% "quite valid", (3) media expert validation with a score of 68 .18% “fairly valid”. The results of the field trials showed: (1) small group trials with a score of 87.5% "very effective" category, (2) cognitive competency test results in large group trials with a a score of 83% "very effective" (3) results in a large group trial response questionnaire with a score of 93.07% in the "very valid" category. The conclusions of the research are: (1) the fun thinkers book learning media was developed with the ASSURE model so that it is appropriate to use social studies learning media in class VII for the 2020/2021 school year; (2) the fun thinker's book media is validated by experts, social studies teachers and has been tested in small and large groups so that they are feasible and effective as learning media in social studies subjects for class VII for 2020/2021. Keywords: Fun thinkers book, IPS subject, Learning media